Polycyclic aromatic hydrocarbons degradation by marine-derived basidiomycetes: optimization of the degradation process - Vieira, Gabriela A.L. [UNESP]; Magrini, Mariana Juventina; Bonugli-Santos, Rafaella C.; Rodrigues, Marili V.N.; Sette, Lara D. [UNESP] (Springer Nature, 2018)
Pyrene and benzo[a]pyrene (BaP) are high molecular weight polycyclic aromatic hydrocarbons (PAHs) recalcitrant to microbial attack. Although studies related to the microbial degradation of PAHs have been carried out in the last decades, little is known about degradation of these environmental pollutants by fungi from marine origin. Therefore, this study aimed to select one PAHs degrader among three marine-derived basidiomycete fungi and to study its pyrene detoxification/degradation. Marasmiellus sp. CBMAI 1062 showed higher levels of pyrene and BaP degradation and was subjected to studies related to pyrene degradation optimization using experimental design, acute toxicity, organic carbon removal (TOC), and metabolite evaluation. The experimental design resulted in an efficient pyrene degradation, reducing the experiment time while the PAH concentration applied in the assays was increased. The selected fungus was able to degrade almost 100% of pyrene (0.08 mg mL−1) after 48 h of incubation under saline condition, without generating toxic compounds and with a TOC reduction of 17%. Intermediate metabolites of pyrene degradation were identified, suggesting that the fungus degraded the compound via the cytochrome P450 system and epoxide hydrolases. These results highlight the relevance of marine-derived fungi in the field of PAH bioremediation, adding value to the blue biotechnology.
Keywords: Acute toxicity; Experimental design; Fungi; Marine biotechnology; PAHs